Blunted Coronary Flow Velocity Reserve is Associated With Impairment in Systolic Function and Functional Capacity in Hypertrophic Cardiomyopathy - Aguiar Rosa, S (2022)
Background Coronary microvascular dysfunction constitutes an important pathophysiological feature in hypertrophic cardiomyopathy (HCM). We aimed to assess the association between impaired coronary flow velocity reserve (CFVR) and ventricular systolic function and functional capacity. Methods Eighty-three patients with HCM were enrolled in this prospective cohort study. Patients underwent echocardiogram to evaluate ventricular performance and CFVR in the left anterior descending artery (LAD) and posterior descending artery (PD). Diastolic coronary flow velocity was measured in basal conditions and in hyperemia. CFVR was calculated as the ratio of hyperemic and basal peak diastolic flow velocities. Functional capacity was evaluated by cardiopulmonary exercise testing (CPET). The link between CFVR and biventricular systolic function and peak VO2 was studied. Results Age was 55.0(14.4)years, 50 patients (60%) were male; 59 patients (71%) had nonobstructive HCM. Mean CFVR LAD was 1.81(0.49) and CFVR PD was 1.73(0.55). Lower CFVR PD was associated with impaired global longitudinal strain (GLS) 2D (β-estimate:-3.240,95%CI:-4.634;-1.846, p < 0.001), GLS 3D (β-estimate:-2.559,95%CI:-3.932;-1.186, p < 0.001) and area strain (β-estimate:-3.044,95%CI:-5.373;-0.716, p = 0.011). Lower values of CFVR PD related to worse global work index (β-estimate:267.824,95%CI:75.964;459.683, p = 0.007), global constructive work (β-estimate:217.300,95%CI:38.750;395.850, p = 0.018) and global work efficiency (β-estimate:5.656,95%CI:2.229;9.084, p = 0.002). Impaired CFVR LAD (β-estimate:2.826, 95%CI:0.913;4.739, p = 0.004) and CFVR PD (β-estimate:2.801,95%CI:0.657;4.945, p = 0.011) were associated with lower TAPSE. Lower values of CFVR LAD (β-estimate:2.580, 95%CI:0.169;4.991, p = 0.036) and CFVR PD (β-estimate:3.163, 95%CI: 0.721;5.606, p = 0.012) were associated with worse peak VO2. Conclusion Lower CFVR was associated with impairment in biventricular systolic function parameters and functional capacity assessed by pVO2.